An Analysis of Linguistic Barriers Affecting Street Vendors’ Communication: A Study at Mandalika Special Economic Development Region of West Nusa Tenggara - Habiburrahman, Habiburrahman; Soepriyanti, Henny; Waluyo, Untung; Nuriadi , Nuriadi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This study explores the linguistic barriers faced by street vendors in Kuta Mandalika, a popular tourist destination in Indonesia, and their impact on communication, job performance, and customer satisfaction. Utilizing a qualitative case study approach, the research subject is 13 street vendors who has an ability to communicate with foreign customer, the research involved semi-structured interviews and observations of street vendors who interact regularly with international tourists, the data analysis will be conducting thematic analysis to analyze the data. The findings highlight several major challenges, including difficulties in understanding foreign accents, limited English vocabulary, pronunciation issues, and reliance on non-verbal communication. The noisy environment where vendors operate further complicates these communication barriers. These linguistic challenges lead to frequent misunderstandings, incorrect orders, and customer dissatisfaction, significantly affecting the vendors' business performance and customer relations. This research is rarely talked by researcher as in the previous study the researcher is focusing on semantic area but that’s quite too deep to learn by street vendors and an English beginner, this approach will contribute to the overall economic vitality of the Mandalika region, benefiting both vendors and the local community.